Effect of bioproducts in the production of Phaseolus vulgaris L. and Arachis hipogea L. - Lambert, Tania; Santiesteban, Ramón; Ceiro, Wilson Geobel; Fernández, Manuel Enrique; López, Guadalupe de las Mercedes; Corrales, Wilson Cristobal (Revista de Ciencias Agrícolas, 2019)
The agrochemical inadequate use to increase the plants yield, is not an environmentally friendly practice. For this reason, the research objective was to evaluate the effect of efficient-microorganisms and chitosan on growth and yield of Phaseolus vulgaris L and Arachis hipogea L. An experiment was established in field at Bayamo municipality, Granma province in the period October/2016 and February/2017. Chitosan (Q) and efficient-microorganisms (EM) alone and combinations were evaluated on the growth and yield of P. vulgaris and A. hipogea. For it, a design of randomized blocks with four replies it was established and an ANOVA and Duncan´s test (p≤0.05) it was used. The results showed that Q+EM combination potentiated the growth and yield of peanuts and bean plants. With Q+EM were obtained the bigger values of gynophores/plant, seeds/plants and weight/100 seeds. Thus, the chitosan + efficient-microorganism’s combination, rise as an biofertilization efficient alternative in the sustainable production of bean and peanuts.